Lyophilized platelets versus cryopreserved platelets for management of bleeding in thrombocytopenic dogs: A multicenter randomized clinical trial. (5th October 2020) - Goggs, Robert; Brainard, Benjamin M.; LeVine, Dana N.; Calabro, Janine; Harrell, Karyn; Mills, Tracy; Stone, Richard; Davidson, Benjamin; Iacovetta, Christine; Harris, Lauren; Gicking, John; Aslanian, Mary; et al.
Abstract: Background: Thrombocytopenia in dogs is common in critical care medicine, but availability of fresh platelet concentrates in veterinary medicine can be limiting. Lyophilized platelets have long shelf‐lives and can be easily transported, stored, and administered in various settings. Objective: To evaluate the efficacy and safety of a novel trehalose‐stabilized canine lyophilized platelet product in thrombocytopenic dogs with clinically‐evident bleeding. Animals: Eighty‐eight dogs with platelet counts <50 × 10 3 /μL and a standardized bleeding assessment tool (DOGiBAT) score ≥2. Methods: Multicenter, randomized, non‐blinded, non‐inferiority clinical trial comparing dimethyl sulfoxide (DMSO)‐stabilized cryopreserved platelet concentrates (CPP) with trehalose‐stabilized lyophilized platelets (LP) for control of bleeding in thrombocytopenic dogs. Dogs were randomized to receive 3 × 10 9 platelets/kg of LP or CPP. Primary outcome measures were change in DOGiBAT score, platelet count, need for additional red cell transfusion and all‐cause mortality. Results: Fifty dogs received LP and 38 received CPP. Baseline demographics and clinical characteristics of both groups were comparable. At 1‐hour post‐transfusion, LP were superior for change in DOGiBAT score, and non‐inferior at 24‐hours post‐transfusion. The LP were non‐inferior to CPP for change in platelet count, need for additional red blood cell units, and survival to discharge. The LP were superior for change in hematocrit at 1‐hour post‐transfusion, and non‐inferior at 24‐hours. No adverse effects were noted in either group. Conclusions and Clinical Importance: A novel trehalose‐stabilized canine LP product appears to be logistically superior and is clinically non‐inferior to DMSO‐stabilized canine CPP for management of bleeding in thrombocytopenic dogs.